2014
DOI: 10.1161/circheartfailure.113.001273
|View full text |Cite
|
Sign up to set email alerts
|

A Bioengineered Hydrogel System Enables Targeted and Sustained Intramyocardial Delivery of Neuregulin, Activating the Cardiomyocyte Cell Cycle and Enhancing Ventricular Function in a Murine Model of Ischemic Cardiomyopathy

Abstract: Background Neuregulin (NRG) is a member of the epidermal growth factor family possessing a critical role in cardiomyocyte development and proliferation. Systemic administration of NRG demonstrated efficacy in cardiomyopathy animal models, leading to clinical trials employing daily NRG infusions. This approach is hindered by requiring daily infusions and off-target exposure. Therefore, this study aimed to encapsulate NRG in a hydrogel (HG) to be directly delivered to the myocardium, accomplishing sustained loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Administration of rNRG1 stimulates cardiomyocyte cycling and proliferation in vitro and myocardial repair in vivo (22, 2830). We used rNRG1 to investigate the effect of stimulating cardiomyocyte cycling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of rNRG1 stimulates cardiomyocyte cycling and proliferation in vitro and myocardial repair in vivo (22, 2830). We used rNRG1 to investigate the effect of stimulating cardiomyocyte cycling.…”
Section: Resultsmentioning
confidence: 99%
“…We (22) and others (2830) have previously demonstrated that rNRG1 stimulates cardiomyocyte proliferation. Thus, administration of rNRG1 stimulates a cellular mechanism that may show a large benefit in pediatric patients.…”
Section: Introductionmentioning
confidence: 81%
“…For in vivo delivery of SHIELD, male adult Wistar rats (Charles River Laboratories) were anesthetized with isoflurane and a left fourth interspace thoracotomy was performed. [25] Fifty μL of SHIELD conjugated with a Cyanine5.5 near-infrared dye (Lumiprobe) was epicardially injected into the anterolateral wall of the left ventricle. SHIELD retention was quantified at 16 days post-injection from explanted hearts (n = 3 per treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, biomaterial injections in peri-infarct zone mainly served to reduce the compliance mismatch between the scar and remote myocardium and consequently promote cell survival and favorable remodeling of the heart. Additionally, numerous studies have demonstrated further therapeutic benefits by incorporation of growth factors (bFGF, TGF-β1, IGF-1, VEGF, Neuregulin-1β) and/or cells in the injected biomaterials [183185]. Many of such studies continue to be performed in small animals, however, studies in larger animal models [186] are required to develop effective treatment strategies with prospect for clinical translation.…”
Section: Therapies For Striated Muscle Disordersmentioning
confidence: 99%